Local Legal Products of The Province of Bali Provincial Government Strengthened and Empowered Local Wisdom - Rideng, I Wayan; Hoesin, Zainal Arifin (Universitas Negeri Malang, 2022)
This study aimed to analyze the empowerment of local wisdom and the form of strengthening local legal products on local wisdom. This study used a socio-legal method with a statutory and conceptual approach. As a result, local wisdom was empowered by developing culture-based industries or small and medium enterprises, developing a pecalang security system, and implementing Balinese Krama, which includes parahyangan, pawongan, and palemahan. Furthermore, article 236 paragraph (4) of Law Number 23 of 2014 strengthened the regional legal products on local wisdom, which explained that regional regulations as one of the regional legal products could contain provisions regarding local wisdom that do not conflict with statutory regulations.